Penciptaan nyanyian folklor Bugis di Desa Watan Leworeng Kecamatan Donri-Donri Kabupaten Soppeng - Andi Agussalim AJ; Azis Azis (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The Community Partnership Program (PKM) partners are Sanggar Sikka Nyili Leworeng Village, Donri-donri District,Soppeng Regency. Two important issues, namely: 1) How is the method of finding ideas or ideas in the creation of Bugis folkloresongs ?; 2) What is the method for processing the creation of Bugis folklore songs? The author uses an approach to the creationof art and literature with the concepts of imitation, aesthetics, and expression. Creation is supported by language and musicelements, including vowels, words, rhythmic, melody, tempo, rhythm, and time. The process of creating folklore songs goesthrough several important stages, which include the stages of exploration, design, and realization. In this process also continuedthe introduction and deeper understanding of folklore singing. The results of the PKM creation of folklore songs, in the form ofsimple folklore songs whose basic ideas come from the form of children's play songs. Overall, the creation of this folklore songexplores the forms of children's play and becomes a work that has creative, unique and aesthetic power. The literary works of artcreated are entitled